MONOGRAPH OF THE FAMILY NEELIDAE COLLEMBOLA - BONET, FEDERICO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1947)
Reducing dextrins were the principal hydrolytic products, glucose being also formed but in much lower proportion The enzymatic activity increases with the concn of the substrate, the best results being obtained at 10% Curves on pH and temp, effects ind
REV SOC MEX HIST NAT
Keywords: MONOGRAPH, FAMILY NEELIDAE COLLEMBOLA; CIENCIAS DE LA VIDA; BIOLOGIA DE LOS INSECTOS (ENTOMOLOGIA); MORFOLOGIA DE LOS INSECTOS